REGISTERED REPORTS AS A METHOD TO INCREASE CREDIBILITY OF SCIENCE – EXPERIMENTAL STUDY AMONG PSYCHOLOGICAL STUDENTS - Sorokowski, Piotr; Groyecka, Agata; Błaszczyński, Kamil; Frąckowiak, Tomasz; Kobylarek, Aleksander (Journal of Education Culture and Society, 2019)
Aims: The modern scientific publishing system suffers from many problems, amongst which one of the most important  is the pressure to publish positive results. A potentially simple way to mitigate publication bias are reviews of manuscript, prior to the data collection and analyses, as well as results presentation and discussion (i.e. Registered Reports).Methods: To test this prediction we conducted a quasi-experiment: two groups of students (n=38), as a part of their academic classes, were asked to design and conduct research projects. They were divided in two groups – Registered Reports- and control group. In both groups students have been encouraged to publish their papers in a local scientific journal.Results: Analyses revealed significant differences in p levels between groups, suggesting more reliable scores for Registered Reports group.Conclusions: Our study partially confirmed the  stated hypothesis and suggested, that registered reports might mitigate publication bias. Future recommendations are advised.